Improving risk adjustment in the Czech Republic - Radovan Chalupka (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper analyses possible options how to improve the risk adjustment of the health insurance system in the Czech Republic. Out of possible options it argues for including Pharmaceutical Cost Groups (PCGs) as additional risk factors since it is an improvement that can be implemented almost instantaneously. On real data from an anonymous sickness fund it confirms that predictive performance of PCGs models is consistently better than the performance of the demographic model that is currently used. The study also describes and examines the Czech health insurance market and implications of proposed changes of the current government. Based on experience from other countries we point to a problem of risk selection if the changes are not accompanies by a tighter regulation, specifically in the form of improved risk adjustment formula.
Keywords: C10; D82; G22; I10; I11; I18; 330; Risk adjustment; Managed competition; Health insurance; Pharmaceutical Cost Groups; Czech Republic; Krankenversicherung; Risikomodell; Wettbewerb; Tschechische Republik